2016
DOI: 10.1088/0952-4746/36/4/r131
|View full text |Cite
|
Sign up to set email alerts
|

Patient radiation doses in paediatric interventional cardiology procedures: a review

Abstract: A large number of investigations into the radiation doses from x-ray guided interventional cardiology procedures in children have been carried out in recent years. A review was conducted of these studies, gathering data on kerma area product (P ), fluoroscopic screening time (FT), air kerma, and estimates of effective dose and organ doses. The majority of studies focus on P and FT with no estimation of dose to the patient. A greater than ten-fold variation in average P was found between different studies, even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 58 publications
0
11
0
1
Order By: Relevance
“…A large variability in radiation exposures among children undergoing CCPs has already been reported in previous studies 7, [25][26][27] . The survey conducted by Cevallos et al, which collected dosimetry information at nine US congenital cardiac catheterization center in 2014-2015, showed ratios of the 95 th percentile to the 50 th percentile values of individual P KA distributions ranging from 4 to 12 depending on the age group for ASD closure (n=289), PDA occlusion (n=445) and pulmonary valvuloplasty (n=250) 26 .…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…A large variability in radiation exposures among children undergoing CCPs has already been reported in previous studies 7, [25][26][27] . The survey conducted by Cevallos et al, which collected dosimetry information at nine US congenital cardiac catheterization center in 2014-2015, showed ratios of the 95 th percentile to the 50 th percentile values of individual P KA distributions ranging from 4 to 12 depending on the age group for ASD closure (n=289), PDA occlusion (n=445) and pulmonary valvuloplasty (n=250) 26 .…”
mentioning
confidence: 77%
“…Other studies have also reported a large individual variability in dosimetry indexes (i.e. fluoroscopy times, P KA ) 25 , but relatively few studies have assessed its impact on organ equivalent doses 7,14,27 . The largest one was conducted at three hospitals in the UK and achieved dose reconstruction for 10,257 diagnostic and therapeutic CCPs performed between 1994 and 2013 7 .…”
mentioning
confidence: 99%
“…These differences are therefore really important and deserve to be explained. Four potential explanations are provided in a recent review by Harbron et al on the patient radiation doses in paediatric interventional cardiology procedures 22 . First, the authors advocated that variations of dose area product may result from a mix of procedure types, each having different complexities and degrees of irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…A summary of conversion factors from DAP to effective dose (CF ED ) are shown in Table 8, which is an adjustment of Table 4 of Harbron et al [13]. Effective dose conversion factors using tissue weighting factors of ICRP publication 60 are also provided in the latter table for comparison with literature.…”
Section: Discussionmentioning
confidence: 99%